2017
DOI: 10.1152/physiolgenomics.00080.2017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-fat diet on secreted milk transcriptome in midlactation mice

Abstract: High-fat diet (HFD) during lactation alters milk composition and is associated with development of metabolic diseases in the offspring. We hypothesized that HFD affects milk microRNA (miRNA) and mRNA content, which potentially impact offspring development. Our objective was to determine the effect of maternal HFD on secreted milk transcriptome. To meet this objective, 4 wk old female ICR mice were divided into two treatments: control diet containing 10% kcal fat and HFD containing 60% kcal fat. After 4 wk on C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 89 publications
5
37
0
Order By: Relevance
“…GO term analysis indicates that these genes were enriched in plasma membrane parts (P value Ͻ 0.001), with Cd14 as the hub gene. In contrast to the work by Chen et al (14), where the authors identified casein genes as the most abundantly expressed mRNAs, we identified no shared genes when comparing the list of DEGs in this study to the top 50 most significantly differentially expressed genes in the milk transcriptome study by Chen et al Out of the list of 1,572 differentially expressed mRNA genes reported by Chen and coauthors, only 21 of them were identified in our study, indicating the unique transcriptome profiles in mammary gland and milk samples during midlactation. Among these, 10 of them showed the same trend of upregulation in our study.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…GO term analysis indicates that these genes were enriched in plasma membrane parts (P value Ͻ 0.001), with Cd14 as the hub gene. In contrast to the work by Chen et al (14), where the authors identified casein genes as the most abundantly expressed mRNAs, we identified no shared genes when comparing the list of DEGs in this study to the top 50 most significantly differentially expressed genes in the milk transcriptome study by Chen et al Out of the list of 1,572 differentially expressed mRNA genes reported by Chen and coauthors, only 21 of them were identified in our study, indicating the unique transcriptome profiles in mammary gland and milk samples during midlactation. Among these, 10 of them showed the same trend of upregulation in our study.…”
Section: Resultsmentioning
confidence: 59%
“…Significant DEGs in our study were compared with the results of previously published work regarding the effect of HFD (from puberty through midlactation) on the murine midlactation milk transcriptome (14). Specifically, we compared our list of DEGs with the top 50 most significant DEGs of the milk transcriptome as well as the complete list of DEGs reported by Chen et al (14). The top 1% of most abundantly expressed genes identified in our study were also compared with these most highly expressed genes reported by this group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, high‐fat diet (HFD) changed microRNA secretion in milk. Notably, development‐associated miR‐142a‐5p, miR‐223‐5p, miR‐10b‐5p, miR‐142a‐3p, and miR‐466d‐3p were differentially impacted by HFD (Chen et al., ). Therefore, dietary patterns in the mothers might impact the microRNA profile, possibly allowing for diagnosis of dietary deviation (for example, malnutrition) or, in the case of microRNA transfer to the infant (Melnik & Schmitz, , ; Zempleni et al., ), altering the potential outcome of milk microRNAs bioactivity.…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 99%
“…Women who consume a diet rich in fat (30% carbohydrate, 55% fat, and 15% protein) showed increased expression of miR-67 and miR-27 in their milk fat globules compared with women on an high-carbohydrate diet (60% carbohydrate, 25% fat, and 15% protein; Munch et al, 2013). Mice that received a diet rich in fat (5.24 kcal/g), showed 25 DE miRNAs compared with mice fed a control diet (3.85 kcal/g; Chen et al, 2017). When cows were fed a diet supplemented with 5% safflower or linseed oil, 22 and 14 miRNAs (7 in common), respec- tively, were differentially expressed in the mammary gland (Li et al, 2015).…”
Section: Influences On Expression Pattern In Milk and Colostrummentioning
confidence: 99%